2010
DOI: 10.1152/jn.00173.2009
|View full text |Cite
|
Sign up to set email alerts
|

Operant Conditioning of Primate Prefrontal Neurons

Abstract: An operant is a behavioral act that has an impact on the environment to produce an outcome, constituting an important component of voluntary behavior. Because the environment can be volatile, the same action may cause different consequences. Thus to obtain an optimal outcome, it is crucial to detect action–outcome relationships and adapt the behavior accordingly. Although prefrontal neurons are known to change activity depending on expected reward, it remains unknown whether prefrontal activity contributes to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 41 publications
2
20
0
Order By: Relevance
“…Second, our results indicate that even relatively unsophisticated animals can generate BCI control signals from non-motor cortex. This extends prior findings that a variety of cortical areas can be used for motor BCI control (Marzullo et al 2006, Kobayashi et al 2010), and may inform ongoing research on PFC plasticity and function. These results were also achieved without prior training on a motor task, suggesting that it is possible to directly train animals on a BCI.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Second, our results indicate that even relatively unsophisticated animals can generate BCI control signals from non-motor cortex. This extends prior findings that a variety of cortical areas can be used for motor BCI control (Marzullo et al 2006, Kobayashi et al 2010), and may inform ongoing research on PFC plasticity and function. These results were also achieved without prior training on a motor task, suggesting that it is possible to directly train animals on a BCI.…”
Section: Discussionsupporting
confidence: 78%
“…There is evidence that PFC neurons specialize in rapid re-configuration to meet task demands (Warden and Miller 2007, Cromer et al 2010). Controllable neurons have been found in primate PFC, although that work selected for neurons that were specifically responding to an existing BCI paradigm (Kobayashi et al 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Animal and human subjects can learn to alter their own brain activity when provided feedback (14). Voluntary control of neuronal activity is likely associated with changes in behavior or cognitive functions, but that relationship is unclear.…”
mentioning
confidence: 99%
“…Voluntary control of neuronal activity is likely associated with changes in behavior or cognitive functions, but that relationship is unclear. Operant control of motor cortical neurons is typically dissociated from movement production (58), and there are no clear behavioral consequences of operant control of neurons in other brain structures (1, 4). Naturally, one might ask whether a chosen control strategy can elicit untrained behavioral or neurophysiological outcomes.…”
mentioning
confidence: 99%
“…Operant conditioning experiments have shown that changes in the firing rates of individual neurons in the motor cortex of monkeys can be elicited [1,2]. In these experiments, the firing rate of the neurons were measured using an implanted electrode, and the monkeys were presented with feedback based on these rates and rewarded for increasing them.…”
mentioning
confidence: 99%